Drop landing exercise does not increase maximum jump height in children - Lulay, A. T.; Bauer, J. J.; Snow, C. M.; Pavol, M. J. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
A 7-month program of repeated drop landing has been shown to increase bone mass in prepubescent children (Fuchs et al., 2001), raising the question of whether these exercises might also have beneficial effects on the neuromuscular system. During landing after a drop from a height, the body's energy is partially absorbed through eccentric contraction of the same muscles that are used in vertical jumping. The eccentric contractions from repeated landings could thus produce an increase in coordinated muscle strength that would allow a child to jump higher. Maximum vertical jump height is known to increase with increased knee extensor strength in young adults (Colliander and Tesch, 1991). This study investigated whether a 7-month program of repeated drop landing would act to increase the maximum vertical jump heights of prepubescent boys and girls. Maximum jump height in these children was highly correlated to BMI (r = -0.56; p < .001); children with lower BMI jumped higher (Figure 1). After accounting for the effects of BMI, there was no difference in maximum jump height between the children who had performed 7 months of drop landing exercises and the children who had not (p = .59; Table 1), independent of sex (p = .98). Maximum jump height also did not differ between boys and girls (p = .42). Finally, maximum jump height was unrelated to age in these children (p = .45). The present results are consistent with a previous study of young men in which two different drop-jump training methods failed to increase vertical jump performance after 6 weeks (Young et al., 1999). It is likely that the drop landings from a 61 cm height did not provide a stimulus of the intensity or specificity needed to produce an increase in the coordinated muscle strength that would lead to higher vertical jumping ability.